2015
DOI: 10.1007/s00784-015-1473-9
|View full text |Cite
|
Sign up to set email alerts
|

Autotransplantation of teeth in humans: a systematic review and meta-analysis

Abstract: Root development of the donor teeth has been established as one the most important factor related to the success of tooth autotransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
172
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(192 citation statements)
references
References 88 publications
8
172
1
11
Order By: Relevance
“…Consequently, teeth with incomplete root formation teeth have a better chance for revascularization due to increased vascularity related to the wider open apices . This concurs with a recent systematic review which reported that although the quality of studies were poor, it could be reasonably concluded that the stage of root development was correlated to the success of the procedure.…”
Section: Discussionsupporting
confidence: 85%
“…Consequently, teeth with incomplete root formation teeth have a better chance for revascularization due to increased vascularity related to the wider open apices . This concurs with a recent systematic review which reported that although the quality of studies were poor, it could be reasonably concluded that the stage of root development was correlated to the success of the procedure.…”
Section: Discussionsupporting
confidence: 85%
“…Autotransplantation involves moving a donor tooth to a receptor site in the same patient ( Figure 2). 53 Not only is autotransplantation a good option because of high success rates, it is also a good option for growing patients who cannot have dental implants placed. [49][50][51][52] Reported complications of autotransplantation include pulp necrosis, root resorption, and hypermobility.…”
Section: Autotransplantationmentioning
confidence: 99%
“…Moreover, the prognosis of splinting types on replanted teeth outcome is not well assessed to date [28].…”
Section: Splintmentioning
confidence: 99%
“…Despite the fact that the splint type should permit physiological movement during the fixation period, recent evidencebased studies demonstrate that splint types do not affect the outcome of the periodontal healing process [24,28].…”
Section: Splintmentioning
confidence: 99%
See 1 more Smart Citation